2008
DOI: 10.1007/s00421-008-0803-x
|View full text |Cite
|
Sign up to set email alerts
|

Swimming training can affect intrinsic calcium current characteristics in rat myocardium

Abstract: Endurance exercise is widely assumed to improve cardiac function in humans, but the mechanisms involved in such changes are not clearly understood. The purpose of this study is to determine whether training elicits adaptations at the level of the L-type Ca(2+) channel. Sprague-Dawley rats performed swimming training at either moderate intensity (MOD) or high intensity (HIGH) during 8 weeks. The trained rats were studied by echocardiography and the whole-cell L-type Ca(2+) currents (I (Ca,L)) characteristics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…2). According to the results of echocardiography measurements, we observed significantly increased LV wall thickness and LV mass index values in exercised animals compared with controls, which is in line with previous studies (2,47). The histomorphometry of LV myocardium showed increased cardiomyocyte diameter (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…2). According to the results of echocardiography measurements, we observed significantly increased LV wall thickness and LV mass index values in exercised animals compared with controls, which is in line with previous studies (2,47). The histomorphometry of LV myocardium showed increased cardiomyocyte diameter (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…finding is consistent with the features described in isolated cardiomyocytes (47,50) as well as in LV myocardium (30) derived from animals that underwent endurance training.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Whereas Mokelke et al (29) studying female SpragueDawley rats trained for 20 wk, found no changes in I CaL , Wang et al (39) reported unchanged I CaL but decreased I CaL density (I CaL /capacitance), apparently due to altered cardiomyocytes morphometry in rats that had undergone swimming training for 8 wk. Both reports differ from ours.…”
Section: Physiological Features: a Lesson From Isolated Cardiomyocytesmentioning
confidence: 99%